Urban restructuring in Cape Town: Redeveloping the Culemborg Rail Yards - Kritzinger, Michaela (School of Architecture, Planning and Geomatics, 2019)
This thesis articulates a vision for how redevelopment in Cape Town's city centre - taking place in the under-utilized Culemborg rail yard and Foreshore precincts - can initiate and contribute to much needed urban restructuring in the city. In recent years, the redevelopment of these areas has been a favourite topic for urban planners and architects in Cape Town. Countless schemes have been proposed, yet none have gained traction. This project's approach differs from that of other plans for the area in that it considers the problem of the disused rail yards and disorganized city centre holistically, within its metropolitan context. It formulates a metropolitan strategy for improving urban performance in Cape Town, and then places the project site within the context of that strategy. In doing so, it makes a broader case for the role of planning in inspiring and guiding urban change that make our cities more equitable, sustainable and better prepared to meet the challenges of an increasingly volatile and uncertain future. This is the ultimate objective of this project: not simply to improve the city's physical design, but to use scarce public resources and land more efficiently, creating opportunity-rich places to live for more people, and spurring economic development in the City. The schematic planning framework proposed in this document shows how, by taking bold action, we can provide the opportunity for over 100,000 Cape Townians to live to in the midst of tremendous economic opportunity. In doing so, huge economic benefits will be reaped, and can be used to crosssubsidized social rental housing, investment in job training and other public institutions and high quality public spaces to be enjoyed by all. This is not a pipe-dream. It will take conviction and vision, to be sure, but it is attainable, and could pave the way for new energy to be injected into a city so desperately in need of transformation.